Hubungan Transformational Leadership Style dan Employee Engagement dengan Organizational Citizenship Behavior Pada Personel Satuan Brigade Mobil Kepolisian Daerah Sumatera Utara - Sucilawati Yano; Muhammad Rajab Lubis; Sjahril Effendy (Universitas Medan Area, 2021)
This study aims to examine: The Relationship between Transformational Leadership Style and Employee Engagement with Organizational Citizenship Behavior in North Sumatra Police Mobile Brigade Unit Personnel. This research is a quantitative study with data collection using a psychological scale in the form of a questionnaire which is then analyzed using multiple regression analysis techniques. Research results a). There is a positive relationship between Transformational Leadership Style and Organizational Citizenship Behavior in North Sumatra Police Mobile Brigade personnel with a correlation coefficient of rx1y = 0.303 and an effective contribution weight of 9.2%. b). There is a positive relationship between Employee Engagement and Organizational Citizenship Behavior, with a correlation coefficient of rx2y = 0.366; with an effective contribution weight of 13.4%. c) There is a positive relationship between Transformational Leadership Style and Employee Engagement with Organizational Citizenship Behavior, with a correlation coefficient of rx1x2y = 0.468, it is concluded that the Transformational Leadership Style and Employee Engagement variables are jointly related to the Organizational Citizenship Behavior variable. The total effective contribution of the two independent variables to Organizational Citizenship Behavior is 21.9%. Based on these results, the hypothesis proposed in this study is accepted.